Traits of professional development of music teachers: construction of teaching and the meaning of relationships and practices in basic education (Orfeu, 2022)
This work comes from a research that had as its general objective to understand how the process of professional development of the music teacher of the region of Natal occurs from its relationship with the school of basic education. The research was carried out from the ideas of the thesis of Author, using also the conceptual vision of Tuan’s place, of Nóvoa’s professional development and of Delory-Momberger’s biographical construction, as well as the autobiographical research. The study was conducted by means of narrative interviews with four professors, experienced and active in basic education schools, thinking the school in the complexity of its spatial dimension. The results indicate that the professional development of music teachers depends on the understanding and recognition of being a teacher in school, the relationship and link between teacher, students and music, and the understanding of what they learn in and with the school.
Keywords: professional development; music teachers; basic education